Review of the Paradigm on the Role of Print Media in Influencing Public Health (Journal of Advances and Scholarly Researches in Allied Education, 2024)
This paper explores important issues related to media research in the context of public health debates and emphasises the requirement of a research plan including media production based on political sciences. Consensus is that via topic selection and presentation, the media significantly impacts public health dialogues and influences public opinions. Often reflecting the interests of strong stakeholders, the way the media presents health challenges, their causes, and solutions greatly influences public health debate. But modern studies often overlook the complex processes of media production necessary for knowledge of how political economics, power, and culture impact these debates.Media production is not just the consequence of linked networks, occupational practices, technology, and institutional contexts reflecting ideological convictions; it is also the output of newsrooms, revealed by a thorough study of media production. Examining non-communicative diseases (NCDs), a major worldwide health concern affected by unsustainable commodity sectors, this viewpoint is very vital. Public health studies have not yet completely revealed the media tactics used by businesses pushing negative items such alcohol, tobacco, and processed foods. Underexplored is the impact of these sectors on public health policy discussions mediated via media coverage.